Berlin : The Monocle travel guide series - Monocle, ....- (Berlin : Gestalten, 2017)
The Monocle Travel Guide o Berlin will take you to our favourite pockets of independent retail and the best places to eat and drink, whether you're after a venerated dining room or a hidden cocktail bar.
Keywords: reisgids